2018
DOI: 10.1016/j.ajic.2018.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and risk factors for mortality in bloodstream infections: A single-center retrospective study in Japan

Abstract: This study reported epidemiology and antimicrobial resistance data of BSIs in Japan and identified several risk factors associated with 30-day mortality. National surveillance of BSIs is required in Japan for comparison with other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
38
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 24 publications
10
38
1
2
Order By: Relevance
“…to those with susceptible bacteria. The dominant risk factor for 30-day all-cause mortality associated with BSI was comorbidity, which agrees with previous studies [3,32,33]. The incidence of BSI and associated 30-day all-cause mortality per 100,000 hospital admissions increased over the study period by 66%, and 17% respectively which is consistent with the results of other studies [4,34,35].…”
Section: Plos Onesupporting
confidence: 92%
See 1 more Smart Citation
“…to those with susceptible bacteria. The dominant risk factor for 30-day all-cause mortality associated with BSI was comorbidity, which agrees with previous studies [3,32,33]. The incidence of BSI and associated 30-day all-cause mortality per 100,000 hospital admissions increased over the study period by 66%, and 17% respectively which is consistent with the results of other studies [4,34,35].…”
Section: Plos Onesupporting
confidence: 92%
“…Surprisingly, multivariable analyses showed a lower 30-day all-cause mortality among patients with BSI caused by AMR bacteria including ESBL, MRSA and VRE without MDR, compared to those with susceptible bacteria [54], while other studies have reported the opposite [32,55,56]. Further studies are needed to explain the lower mortality rate found in this group.…”
Section: Plos Onementioning
confidence: 61%
“…CBSIs occur in up to 10% of all bloodstream infections in hospitalized patients [313,314,315], and the mortality rate is about 40% [316,317]. Normally, this mortality is higher than in bloodstream infections involving bacteria [326,327]. Risk factors for CBSIs include critically ill patients in intensive care units, DM, immunosuppressive states, mechanical ventilation, neutropenia, recent surgical procedures, and prematurity [315,318,319].…”
Section: Candidiasis and Dmmentioning
confidence: 99%
“…Similarly, Japan has shown a varying pathogenic profile of BSIs, with E. coli, S. aureus, Streptococcus spp., and Klebsiella spp. as the common organisms [24]. These differing reports on BSI-causing pathogens explain the variations in different regions.…”
Section: Plos Onementioning
confidence: 99%